Relating to the Organization, Government, etc., of the State Militia, Ch. 359, § 1 in State of Kansas: Session Laws (1903). - (:unkn) unknown (General Publisher, 1903)
No armed military force from another state or territory shall be permitted to enter the state without his permission, unless such military force is a part of the United States army or is acting under the authority of the United States. No independent military organization, except it is [sic] a corps of cadets at an educational institution, shall be permitted to bear arms without first securing permission from the commander-in-chief.
--
Keywords: MILITIAS